2021
DOI: 10.1016/j.clbc.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Final Efficacy Results of Neratinib in HER2-positive Hormone Receptor-positive Early-stage Breast Cancer From the Phase III ExteNET Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 28 publications
5
142
0
11
Order By: Relevance
“…In the randomized phase III trial, ExteNET, demonstrated that 1 year of adjuvant neratinib after chemotherapy plus trastuzumab contributes to significant better PFS in operable breast cancer (hazard ratio, 0.73; 95% CI 0.57–0.92, p = 0.0083) [ 107 ]. The cumulative incidence of CNS recurrences was fewer in the neratinib group (0.7% with neratinib, 2.1% with placebo, respectively) in the HR-positive patients who initiated the study treatment within 1 year of prior trastuzumab [ 108 ].…”
Section: Systemic Therapy For Bcbmmentioning
confidence: 99%
“…In the randomized phase III trial, ExteNET, demonstrated that 1 year of adjuvant neratinib after chemotherapy plus trastuzumab contributes to significant better PFS in operable breast cancer (hazard ratio, 0.73; 95% CI 0.57–0.92, p = 0.0083) [ 107 ]. The cumulative incidence of CNS recurrences was fewer in the neratinib group (0.7% with neratinib, 2.1% with placebo, respectively) in the HR-positive patients who initiated the study treatment within 1 year of prior trastuzumab [ 108 ].…”
Section: Systemic Therapy For Bcbmmentioning
confidence: 99%
“…Since neratinib proved to be particularly effective in hormone receptor positive (HR+) cancers and when therapy was initiated within one year following trastuzumab (HR+ population/treatment initiated ≤ 1 year), approval in the US and Europe was granted with the corresponding restrictions. Further subgroup analyses after 8 years of follow-up were presented at the SABCS in December 2020 and recently published [80]. In the HR+/therapy start ≤ 1 year population, the 5-year iDFS rate was 90.8 vs. 85.7 % in the neratinib arm (delta 5.1 %, HR = 0.58; 95 % CI: 0.41-0.82).…”
Section: Palbociclib In Patients Without Pcr After Neoadjuvant Chemotherapy and High Risk Of Relapsementioning
confidence: 99%
“…Als besonders wirksam erwies sich Neratinib bei hormonrezeptorpositiven (HR+) Karzino-men und bei Therapiestart binnen eines Jahres nach Trastuzumab (Population HR+/Therapiestart ≤ 1 Jahr), sodass die Zulassung in den USA und Europa mit entsprechenden Einschränkungen folgte. Auf dem SABCS wurden im Dezember 2020 weitere Subgruppenanalysen nach 8 Jahren Nachbeobachtung vorgestellt und kürzlich publiziert [80]. In der Population HR+/Therapiestart ≤ 1 Jahr lag die 5-Jahres-iDFS-Rate im Neratinib-Arm bei 90,8 vs. 85,7 % (delta 5,1 %, HR = 0,58; 95 %-KI: 0,41-0,82).…”
Section: Neratinib Nach (Neo-)adjuvanter Therapie Des Her2-positiven Mammakarzinomsunclassified
“…tumours who started treatment B 1 year of completing trastuzumab (HR?/ B 1-year population) (Fig. 3; [29]). Among patients with HR?…”
Section: Use Of Neratinib In the Extended Adjuvant Settingmentioning
confidence: 99%
“…2 ExteNET study design [27]. CNS central nervous system; DCIS ductal carcinoma in situ; DFS disease-free survival; EQ-5D EuroQoL 5-dimension; ER oestrogen receptor; FACT-B Functional Assessment of Cancer Therapy-Prostate; HER2?, human epidermal growth factor receptor 2-positive; iDFS invasive disease-free survival; IHC immunohistochemistry; OS overall survival; PR progesterone receptor Subsequent analysis of CNS recurrence data in a HR?/ B 1-year population and in a subgroup of patients of clinical interest in the ExteNET study has also suggested that neratinib may reduce the risk of brain metastases [29]. Although the between-group differences did not reach statistical significance in these patient subgroups, the cumulative incidence of CNS recurrence was numerically lower in the neratinib arm at 5 years (0.7% vs. 2.1% with placebo).…”
Section: Use Of Neratinib In the Extended Adjuvant Settingmentioning
confidence: 99%